2010
DOI: 10.1111/j.1365-2966.2009.16204.x
|View full text |Cite
|
Sign up to set email alerts
|

Probing evolutionary mechanisms in galaxy clusters: neutral atomic hydrogen in Abell 1367

Abstract: We present Very Large Array H i imaging data for a field in the NW of the galaxy cluster Abell 1367 (z= 0.02) in an attempt to probe the effect environment has on the interstellar medium of late‐type spiral galaxies. Several galaxies, like CGCG 097–087, show pronounced tails and asymmetries, and seven out of 10 show significant, several kpc offsets between the H i centroid and the optical. We compare our results against a sample of optically bright, late‐type galaxies (spirals) across the central 1.5 Mpc of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 80 publications
(183 reference statements)
3
62
0
Order By: Relevance
“…Similar results are observed for the Coma cluster (25), in which a 65-kpc tail is seen in the member galaxy NGC 4848, suggesting ram pressure stripping on radial infall of the galaxy on its first passage through the cluster. Long tails of HI gas and ionized gas are also observed in the cluster Abell 1367, revealing galaxies in the process of being stripped-out of their gas (26,27). Kenney and colleagues (24) provide a detailed observational study of the transformation of a Virgo cluster dwarf irregular galaxy into a dwarf elliptical by ram pressure stripping; the observations show a long tail of gas clumps being accelerated by ram pressure and leaving behind streams of new stars, nicely consistent with ram pressure stripping by the intracluster gas.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results are observed for the Coma cluster (25), in which a 65-kpc tail is seen in the member galaxy NGC 4848, suggesting ram pressure stripping on radial infall of the galaxy on its first passage through the cluster. Long tails of HI gas and ionized gas are also observed in the cluster Abell 1367, revealing galaxies in the process of being stripped-out of their gas (26,27). Kenney and colleagues (24) provide a detailed observational study of the transformation of a Virgo cluster dwarf irregular galaxy into a dwarf elliptical by ram pressure stripping; the observations show a long tail of gas clumps being accelerated by ram pressure and leaving behind streams of new stars, nicely consistent with ram pressure stripping by the intracluster gas.…”
Section: Resultsmentioning
confidence: 99%
“…Long tails of HI and ionized gas are observed in galaxies in several nearby clusters, consistent with the description given here (e.g., refs. 21,22,[25][26][27].…”
mentioning
confidence: 99%
“…Assuming that their speed to the parent galaxy is 1000 km s −1 , they should have survived in the cluster environment for 70 Myrs. As no counterpart is found near the clouds in H I survey of Abell 1367 (Scott et al 2010), it is rather unlikely that the orphan clouds are re-ionized portions of a long tail, such as the long tail of NGC 4388 in the Virgo cluster (Yoshida et al 2002;Oosterloo & van Gorkom 2005).…”
Section: Orphan Cloudsmentioning
confidence: 99%
“…CGCG 097-073 and CGCG 097-079 are well known with their prominent tails (e.g., Gavazzi & Jaffe 1987;Gavazzi 1989;Boselli et al 1994;Gavazzi et al 1995Gavazzi et al , 1998Gavazzi et al , 2001aScott et al 2010). In , we showed a preliminary image from the data in this study.…”
Section: Newly Detected Extended Ionized Gas Clouds (Eigs)mentioning
confidence: 99%
“…While there are also examples of longer ram pressure stripped gas tails (length ∼ (1 − 2) × D 25 ; Oosterloo & van Gorkom 2005;Chung et al 2007;Boselli et al 2016), most of the gas missing in the Virgo galaxies has not been revealed in the intracluster space (e.g., Vollmer & Huchtmeier 2007). In the more distant cluster A1367, with about 5-times the Virgo mass, several long RPS tails were observed in H I (Scott et al 2010(Scott et al , 2012.…”
Section: Introductionmentioning
confidence: 99%